Preparation method and application of dandelion spherical NiCoSe and CC and Ni (OH) 2 composite electrode material

By synthesizing dandelion spherical NiCoSe@CC@Ni(OH)2 composite nanomaterials, the problems of insufficient conductivity and cyclic stability of existing electrode materials are solved, higher conductivity and cyclic stability are achieved, and the electrochemical performance of supercapacitors is improved.

CN119517634APending Publication Date: 2025-02-25JIANGSU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411650841.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The insufficient conductivity and cyclic stability of existing electrode materials in the energy storage field hinder their practical application in supercapacitors.

Method used

Dandelion spherical NiCoSe@CC@Ni(OH)2 composite nanomaterial was synthesized by hydrothermal method, immersion method and post-burning tube furnace selenization method. Using carbon cloth as the substrate material, NiCoSe and Ni(OH)2 were directly grown in situ on it to form a composite electrode material.

Benefits of technology

It improves the conductivity and cyclic stability of the material, enhances flexibility, reduces impedance, provides more ion-contact specific surface area and reactive sites, significantly improving electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517634A_ABST
    Figure CN119517634A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of composite electrode materials, and relates to a dandelion spherical NiCoSe-CC-Ni (OH) 2 composite electrode material preparation method, which comprises: dissolving a cobalt source, a nickel source, urea and hexadecyl trimethyl ammonium bromide in deionized water, and violently stirring to form a transparent solution; immersing in carbon cloth, transferring to a high-pressure reaction kettle, and carrying out hydrothermal reaction at 140-180 DEG C for 6-18 hours to obtain a NiCo-coated CC precursor; the preparation method comprises the following steps: adding a NiCo-CC precursor into a Lewis acid solution, etching for 3-9 hours, cleaning, and drying at 60 DEG C to obtain a precursor NiCo-CC-Ni (OH) 2; and putting the precursor NiCo (at) CC (at) Ni (OH) 2 at the downstream of the tubular furnace, and carrying out chemical vapor deposition selenylation in an argon atmosphere to obtain the NiCo (at) CC (at) Ni (OH) 2. According to the invention, the carbon cloth is used as a substrate, so that the flexibility and the conductivity of the material are enhanced to a great extent, and meanwhile, NiCoSe-coated CC-coated Ni (OH) 2 directly grows on the carbon cloth in situ, so that the use of an adhesive is avoided, the impedance of the material is reduced, the contact specific surface area of ions can be maximized, and a large number of reactive active sites are provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode materials, relates to a composite electrode, and in particular to a preparation method and application of a dandelion ball-shaped NiCoSe@CC@Ni(OH)2 composite electrode material. Background Art

[0002] The rapid surge in available resources caused by the advent of industrialization and construction has led to the earth's energy consumption gradually failing to meet production needs. In this context, it is imperative to identify and implement sustainable renewable energy sources to meet these pressing challenges. It is well known that solar, wind, geothermal, and tidal energy are potential clean renewable energy sources. However, in order to achieve sustainable utilization of these resources, they must be converted into practical forms such as electricity. The superior properties of supercapacitors (SCs), including fast charge and discharge rates, high power density, and excellent cycle life, make them highly favored in various applications. According to the charge storage mechanism, supercapacitors can be divided into electric double layer capacitors (EDLCs) and redox pseudocapacitors. As a special pseudocapacitive electrode material, layered double hydroxides (LDHs) have attracted great attention due to their structural similarity to hydrotalcite or synthetic anionic clays such as Ni and Co hydroxides / oxides. Related literature shows that LDHs have rich theoretical capacity and exhibit manipulable and versatile nanostructures and morphologies. However, the disadvantage is that they are not stable enough. At the same time, despite the presence of a large number of active sites, the slow charging speed hinders the effective utilization of their actual capacity and rate capabilities. Therefore, compounding LDHs with materials with excellent electrical conductivity, such as graphene, carbon, and metallic substances, is a feasible approach to address the limitations of LDHs.

[0003] In recent years, a lot of research has been done in the field of energy storage due to the excellent electrochemical properties of transition metal oxides and sulfides. However, the conductivity and cycle stability of existing materials are still unsatisfactory, which hinders further development. In the periodic table, the elements Se, S and O belong to the same group. The conductivity of Se is much higher than that of O and S, which makes transition metal selenides exhibit excellent conductivity and high specific capacity when used as electrode materials. In particular, bimetallic nickel cobalt selenide as an electroactive material for HSC has attracted much attention due to its excellent conductivity, high electrochemical activity, rich redox reactions and low cost. Ni 2+ and Co 2+ The synergistic effect of ions is more conducive to adjusting the electronic structure and promoting conductivity, making bimetallic nickel cobalt selenide exhibit better electrochemical performance than single metal selenide.

[0004] Ni(OH)2 is considered to be a good candidate and has been widely studied. Because it has ultra-high theoretical capacity, excellent electrochemical activity and low cost. However, it is difficult to obtain such a high specific capacitance in practical applications due to poor conductivity and cycle performance. Therefore, a measure to solve the above problems is to combine Ni(OH)2 with transition metal compounds to construct composite materials to improve their electrochemical properties. Considering the advantages of nickel cobalt selenide and Ni(OH)2, the advantages of bimetallic (Ni,Co)Se2 and Ni(OH)2 are combined, and the advantages of each component are realized through complementarity and synergy, the electrochemical performance is effectively improved, and high-performance nanocomposites are developed. Summary of the invention

[0005] In order to overcome the defects of the prior art, an object of the present invention is to disclose a method for preparing a dandelion ball-shaped NiCoSe@CC@Ni(OH)2 composite electrode.

[0006] Technical Solution

[0007] Using cobalt source, nickel source, urea (CO(NH2)2), hexadecyltrimethylammonium bromide (CTAB), carbon cloth (CC), deionized water and selenium powder as raw materials, NiCo@CC was first obtained by hydrothermal method, then NiCo@CC@Ni(OH)2 composite nanomaterials were synthesized by soaking, and finally NiCoSe@CC@Ni(OH)2 composite nanomaterials were synthesized by selenization.

[0008] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0009] A. Dissolve the cobalt source, nickel source, urea and hexadecyltrimethylammonium bromide in deionized water and stir vigorously to form a transparent solution, wherein the material ratio of the cobalt source, nickel source, urea, hexadecyltrimethylammonium bromide and deionized water is 2-6mM:1-3mM:16-48mg:36.9-110.7mg:25-75

[0010] mL, preferably 4mM:2mM:32mg:72.8mg:50mL;

[0011] B. Immerse the carbon cloth in the transparent solution, move to a high-pressure reactor, perform hydrothermal reaction at 140-180°C for 6-18h, preferably at 160°C for 12h, cool naturally to room temperature, filter, wash with ethanol and deionized water, and dry at 60°C for 24h to obtain a NiCo@CC precursor;

[0012] C. Prepare a Lewis acid solution by dissolving 3.2g Ni(NO3)2·6H2O in 10ml ethanol, add NiCo@CC precursor, etch for 3-9h, preferably 6h, take out, wash with ethanol and deionized water, and dry at 60℃ to obtain the precursor NiCo@CC@Ni(OH)2;

[0013] D. Place the precursor NiCo@CC@Ni(OH)2 in the downstream of the tube furnace and the selenium powder in the upstream of the tube furnace. The mass ratio of the precursor to the selenium powder is 1:2. In an argon atmosphere, heat the furnace at a rate of 10~30 rpm.

[0014] The reaction mixture is calcined at a rate of 15°C, 300-400°C for 2-3h, preferably 350°C for 2.5h, and chemical vapor deposition selenization is performed to obtain the product.

[0015] According to a preferred embodiment of the present invention, in step A, the cobalt source is Co(NO3)2 or CoCl2, preferably Co(NO3)2; the nickel source is Ni(NO3)2 or NiCl2, preferably Ni(NO3)2.

[0016] In a preferred embodiment of the present invention, in step B, the carbon cloth is pretreated and cut into pieces with a size of 1×2 cm. 2 , and ultrasonicated in acetone, ethanol, and deionized water for 1 h respectively to remove surface impurities.

[0017] According to the method of the present invention, the prepared NiCoSe@CC@Ni(OH)2 composite nanomaterial has a microscopic morphology of a dandelion-shaped structure on the surface of the carbon cloth.

[0018] Another purpose of the present invention is to use the prepared NiCoSe@CC@Ni(OH)2 composite nanomaterial as a supercapacitor electrode material.

[0019] The prepared NiCoSe@CC@Ni(OH)2 composite nanomaterial was used as the positive electrode material, KOH with a molar concentration of 6 mol / L was used as the electrolyte, and the activated carbon, conductive carbon black and binder were uniformly mixed and dispersed in the solvent at a mass ratio of 8:1:1, and then coated on the nickel foam, dried, and pressed to prepare the electrode sheet as the negative electrode material of the capacitor. The electrochemical performance tests such as cyclic voltammetry (CV) and constant current charge and discharge were carried out in the two-electrode system, and the corresponding energy density and power density were calculated to evaluate the electrochemical performance of the prepared NiCoSe@CC@Ni(OH)2 composite nanomaterial. The voltage range of the cyclic voltammetry (CV) test was 0-0.5V, the scan speed was 2, 5, 10, 20, 50 and 100mV / s, and the voltage range of the constant current charge and discharge test was 0-0.5V, and the current density was 1, 2, 3, 5, 8 and 10A / g.

[0020] The NiCoSe@CC@Ni(OH)2 composite nanomaterial prepared in the present invention is subjected to structural analysis and performance analysis using instruments such as an X-ray diffractometer (XRD) and a CHI760E electrochemical workstation to evaluate its electrochemical activity.

[0021] Carbon cloth (CC) is a flexible carbon material made of several carbon fibers woven together in the horizontal and vertical directions. It has the advantages of strong conductivity, good mechanical flexibility and high chemical stability, and can be a good carrier of active substances.

[0022] The reactants and reagents used in the present invention are all commercially available.

[0023] Beneficial Effects

[0024] The present invention synthesizes NiCoSe@CC@Ni(OH)2 composite nanomaterials by three steps: hydrothermal method, immersion method and post-firing tube furnace selenization method. The carbon cloth as the substrate greatly enhances the flexibility and conductivity of the material. At the same time, NiCoSe@CC@Ni(OH)2 grows directly on the carbon cloth in situ, avoiding the use of adhesives, reducing the impedance of the material, maximizing the ion-accessible specific surface area, and providing a large number of active sites for reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 .Scanning electron microscope image of the NiCoSe@CC@Ni(OH)2 composite electrode material prepared in Example 2;

[0026] Figure 2 . GCD curve of NiCoSe@CC@Ni(OH)2 composite electrode material prepared in Example 2;

[0027] Figure 3 .Energy density-power density diagram of supercapacitor assembled with NiCoSe@CC@Ni(OH)2 composite electrode material prepared in Example 2;

[0028] Figure 4 .Cycling stability diagram of supercapacitor assembled with NiCoSe@CC@Ni(OH)2 composite electrode material prepared in Example 2. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with the embodiments so that those skilled in the art can better understand the present invention, but the present invention is not limited to the following embodiments.

[0030] Unless otherwise defined, the terms (including technical terms) used herein should be interpreted as having the same meaning as commonly understood by those skilled in the art to which the present invention belongs. It will also be understood that the terms used herein should be interpreted as having the meaning consistent with their meanings in the content of this specification and related technologies, and should not be interpreted in an idealized or excessive form unless specifically defined as such herein.

[0031] Example 1

[0032] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0033] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a transparent solution; move to a 100mL high-pressure reactor and put in a piece of carbon cloth, perform hydrothermal reaction at 160°C for 12h, cool naturally to room temperature, filter the precipitate, wash with ethanol and deionized water 3 times, and dry at 60°C for 24h to obtain NiCo@CC precursor;

[0034] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare a Lewis acid solution, add the prepared NiCo@CC precursor, and etch for 6 hours; take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried composite material downstream of a tube furnace, and place selenium powder upstream of the tube furnace. According to the mass ratio of the precursor to the selenium powder of 1:2, in an argon atmosphere, heat up by 10°C per minute, and keep the chemical vapor deposition selenization at 350°C for 2.5 hours to obtain a NiCoSe@CC@Ni(OH)2 composite electrode material.

[0035] Characterization and analysis of NiCoSe@CC@Ni(OH)2 composite electrode materials

[0036] like Figure 1 As shown in the figure, we can see that the NiCoSe@CC@Ni(OH)2 composite electrode material has a dandelion-shaped structure composed of needles in a microscopic state and is evenly distributed on the carbon cloth.

[0037] like Figure 2 As shown, the GCD curve of NiCoSe@CC@Ni(OH)2 composite electrode material can be seen from the figure.

[0038] like Figure 3As shown, the NiCoSe@CC@Ni(OH)2 composite electrode material prepared in this embodiment is used as a supercapacitor electrode material for the application of a two-electrode system. From the energy density-power density diagram, it can be seen that the assembled supercapacitor has good power density and energy density. When the maximum energy density reaches 46.8Wh / kg, its power density is 800W / kg.

[0039] like Figure 4 As shown, the prepared NiCoSe@CC@Ni(OH)2 composite electrode material was used as the positive electrode material for the cycle stability test. After 10,000 cycles, its specific capacitance maintained 82.37% of the initial capacity.

[0040] Example 2

[0041] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0042] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, and carry out a hydrothermal reaction in an electric constant temperature blast drying oven at 160°C for 12h. After the reaction is completed, wait for the reactor to cool to room temperature, filter the precipitate, wash it with ethanol and deionized water three times, and dry it in a constant temperature drying oven at 60°C for 24h to obtain a NiCo@CC precursor;

[0043] Step 2: Dissolve 3.2g Ni(NO3)2·6H2O in 10ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and keep Lewis acid etching reaction for 3h. After the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in a 60℃ oven to obtain the precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of the tube furnace, and place the selenium powder upstream of the tube furnace in an argon atmosphere, heat it up by 15℃ per minute, and keep the chemical vapor deposition selenization at 350℃ for 3h to obtain it.

[0044] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its maximum energy density reaches 44.3.1Wh / kg and its power density is 800W / kg.

[0045] Example 3

[0046] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0047] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, and perform a hydrothermal reaction in an electric constant temperature blast drying oven at 160°C for 12h; after the reaction, wait for the reactor to cool to room temperature, filter the precipitate, wash it with ethanol and deionized water three times, and dry it in a constant temperature drying oven at 60°C for 24h to obtain a NiCo@CC precursor;

[0048] Step 2: Dissolve 3.2g Ni(NO3)2·6H2O in 10ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and keep Lewis acid etching reaction for 9h. After the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in a 60℃ oven to obtain the precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of the tube furnace, and place the selenium powder upstream of the tube furnace in an argon atmosphere, heat it up by 15℃ per minute, and keep the chemical vapor deposition selenization at 350℃ for 3h to obtain it.

[0049] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 40.8Wh / kg.

[0050] Example 4

[0051] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0052] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, and carry out a hydrothermal reaction in an electric constant temperature blast drying oven at 160°C for 12h; after the reaction is completed, wait for the reactor to cool to room temperature, filter the precipitate, wash it with ethanol and deionized water three times, and dry it in a constant temperature drying oven at 60°C for 24h to obtain a NiCo@CC precursor;

[0053] Step 2: Dissolve 3.2g Ni(NO3)2·6H2O in 10ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and keep Lewis acid etching reaction for 6h. After the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in a 60℃ oven to obtain the precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of the tube furnace, and place the selenium powder upstream of the tube furnace in an argon atmosphere, heat up by 15℃ per minute, and keep the chemical vapor deposition selenization at 400℃ for 2.5h to obtain the product.

[0054] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 42.7Wh / kg.

[0055] Example 5

[0056] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0057] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 140°C for 12h, and after the reaction, naturally cool to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0058] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2.5 hours to obtain the product.

[0059] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 43.1Wh / kg.

[0060] Example 6

[0061] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0062] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 180°C for 12h, and after the reaction, cool naturally to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0063] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2.5 hours to obtain the product.

[0064] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 42.3Wh / kg.

[0065] Example 7

[0066] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0067] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 160°C for 6h, and after the reaction, cool naturally to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0068] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2.5 hours to obtain the product.

[0069] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 40.1Wh / kg.

[0070] Example 8

[0071] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0072] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 160°C for 18h, and after the reaction, cool naturally to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0073] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2.5 hours to obtain the product.

[0074] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 40.6Wh / kg.

[0075] Example 9

[0076] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0077] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 160°C for 12h, and after the reaction, cool naturally to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0078] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2 hours to obtain the product.

[0079] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 43.9Wh / kg.

[0080] Example 10

[0081] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0082] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 160°C for 12h, and after the reaction, cool naturally to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0083] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 3 hours to obtain the product.

[0084] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 42.4Wh / kg.

[0085] Embodiment 11

[0086] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0087] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, and perform a hydrothermal reaction in an electric constant temperature blast drying oven at 160°C for 12h; after the reaction, wait for the reactor to cool to room temperature, filter the precipitate, wash it with ethanol and deionized water three times, and dry it in a constant temperature drying oven at 60°C for 24h to obtain a NiCo@CC precursor;

[0088] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare a Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain the Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in a 60°C oven to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 300°C for 2.5 hours to obtain the product.

[0089] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 39.3Wh / kg.

[0090] Example 12

[0091] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0092] Step 1, weigh 4mM Co(NO3)2·6H2O, 2mM Ni(NO3)2·6H2O, 32mg urea, 78.2mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, and perform a hydrothermal reaction in an electric constant temperature blast drying oven at 160°C for 12h; after the reaction, wait for the reactor to cool to room temperature, filter the precipitate, wash it with ethanol and deionized water three times, and dry it in a constant temperature drying oven at 60°C for 24h to obtain a NiCo@CC precursor;

[0093] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare a Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain the Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 400°C for 2.5 hours to obtain the product.

[0094] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 38.6Wh / kg.

[0095] Example 13

[0096] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0097] Step 1, weigh 4mM CoCl2·6H2O, 2mM NiCl2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, perform a hydrothermal reaction at 160°C for 6h, and after the reaction, cool naturally to room temperature, filter the precipitate, wash it with ethanol and deionized water 3 times, and dry it at 60°C for 24h to obtain a NiCo@CC precursor;

[0098] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in an oven at 60°C to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace under an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2.5 hours to obtain the product.

[0099] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 37.8Wh / kg.

[0100] Embodiment 14

[0101] A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material comprises the following steps:

[0102] Step 1: Weigh 4mM CoCl2·6H2O, 2mM NiCl2·6H2O, 32mg urea, 72.8mg hexadecyltrimethylammonium bromide, dissolve in 50mL deionized water, and stir vigorously to form a uniformly dispersed solution; then transfer the solution to a 100mL high-pressure reactor and add a piece of carbon cloth, and perform a hydrothermal reaction in an electric constant temperature blast drying oven at 160°C for 12h. After the reaction is completed, wait for the reactor to cool to room temperature, filter the precipitate, wash it with ethanol and deionized water three times, and dry it in a constant temperature drying oven at 60°C for 24h to obtain a NiCo@CC precursor;

[0103] Step 2: Dissolve 3.2 g Ni(NO3)2·6H2O in 10 ml ethanol solution to prepare a Lewis acid solution, add it to the prepared NiCo@CC composite material, and maintain the Lewis acid etching reaction for 6 hours; after the reaction, take out the precursor, wash it with ethanol and deionized water for 3-5 times, and dry it in a 60°C oven to obtain a precursor NiCo@CC@Ni(OH)2 composite material; place the dried product downstream of a tubular furnace, and place selenium powder upstream of the tubular furnace in an argon atmosphere, heat it by 15°C per minute, and maintain chemical vapor deposition selenization at 350°C for 2.5 hours to obtain a NiCoSe@CC@Ni(OH)2 composite nanomaterial.

[0104] The prepared NiCoSe@CC@Ni(OH)2 / composite electrode material is used as a supercapacitor electrode material, and its power density is 800W / kg when the maximum energy density reaches 38.4Wh / kg.

[0105] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material, characterized in that: The following steps are involved: A. dissolving a cobalt source, a nickel source, urea and hexadecyltrimethylammonium bromide in deionized water and stirring vigorously to form a transparent solution, wherein the material ratio of the cobalt source, the nickel source, the urea and the hexadecyltrimethylammonium bromide to the deionized water is 2-6mM: 1-3mM: 16-48mg: 36.9-110.7mg: 25-75mL; B. Immerse the carbon cloth in the transparent solution, move to a high-pressure reactor, perform hydrothermal reaction at 140-180°C for 6-18 hours, cool naturally to room temperature, filter, wash with ethanol and deionized water, and dry at 60°C for 24 hours to obtain a NiCo@CC precursor; C. Prepare Lewis acid solution in the ratio of 3.2g Ni(NO3)2·6H2O dissolved in 10ml ethanol, add NiCo@CC precursor, etch for 3-9h, take out, wash with ethanol and deionized water, dry at 60℃ to obtain precursor NiCo@CC@Ni(OH)2; D. Place the precursor NiCo@CC@Ni(OH)2 downstream of the tube furnace and the selenium powder upstream of the tube furnace. With the mass ratio of the precursor to the selenium powder being 1:2, calcine at 300-400℃ for 2-3h in an argon atmosphere at a heating rate of 10-15℃ per minute to obtain chemical vapor deposition selenization.

2. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step A, the cobalt source is Co(NO3)2 or CoCl2, preferably Co(NO3)2.

3. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step A, the nickel source is Ni(NO3)2 or NiCl2, preferably Ni(NO3)2.

4. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step A, the material ratio of the cobalt source, the nickel source, urea, hexadecyltrimethylammonium bromide and deionized water is 4mM:2mM:32mg:72.8mg:50mL.

5. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step B, the carbon cloth is immersed in the transparent solution, moved to a high-pressure reactor, subjected to hydrothermal reaction at 160° C. for 12 h, and then naturally cooled to room temperature.

6. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step B, the carbon cloth is pretreated and cut into pieces with a size of 1×2 cm 2 , ultrasonically treated in acetone, ethanol and deionized water for 1 h respectively to remove surface impurities.

7. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step C, the NiCo@CC precursor is added and etched for 6 hours.

8. The method for preparing the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material according to claim 1, characterized in that: In step D, chemical vapor deposition selenization is performed in an argon atmosphere at a temperature increase rate of 10-15° C. per minute and calcined at 350° C. for 2.5 hours.

9. The dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material prepared according to any one of claims 1 to 8 is characterized in that: Its microscopic morphology is a dandelion-shaped structure on the surface of the carbon cloth.

10. An application of the dandelion-shaped NiCoSe@CC@Ni(OH)2 composite electrode material as claimed in claim 9, characterized in that: It is used as a supercapacitor electrode material.